A Response to “Predictors of Intention to Get a COVID-19 Vaccine of Health Science Students: A Cross-Sectional Study.” [Letter] - Gupta A; Raymond RJ (Dove Medical Press, 2021)
Aanchal Gupta, Roshan Jonash Raymond Barts and The London School of Medicine and Dentistry, London, UKCorrespondence: Aanchal GuptaBarts and The London School of Medicine and Dentistry, Garrod Building, Turner Street, Whitechapel, London, E1 2AD, UKTel +44 7946769695Email a.gupta@smd16.qmul.ac.uk View the original paper by Professor Nguyen and colleagues